Integrating cultural dimensions into a cognitive affective model for LMS user satisfaction in Indonesia’s higher education institution - Melati Salma; Ari Widyanti; Muhammad Hudzaly Hatala; Eka Pratiwi Briant Pakiding; Ilham Darmawan; Laila Nafisah (OPSI, 2026)
This study investigates how cultural dimensions are integrated into a cognitive-affective model to explain user satisfaction with Learning Management System (LMS) interfaces in Indonesian higher education. Using PLS-SEM with data from 348 university students across Indonesia, the study examined the effects of cognitive factors, affective factors, and cultural dimensions on satisfaction. The results show that Classical Aesthetic significantly influences Efficiency (β = 0.755, t = 29.767, p < 0.05), Expressive Aesthetic (β = 0.752, t = 32.485, p < 0.05), and Satisfaction (β = 0.185, t = 2.559, p = 0.011). Efficiency positively affects Effectiveness (β = 0.744, t = 25.889, p < 0.05) and Satisfaction (β = 0.298, t = 4.667, p < 0.05), while Effectiveness also contributes to Satisfaction (β = 0.273, t = 4.684, p < 0.05). Expressive Aesthetic strongly predicts Playfulness (β = 0.804, t = 37.624, p < 0.05), but Playfulness does not meaningfully affect Satisfaction (β = 0.066, t = 1.364, p = 0.172). Power Distance has a significant positive effect on Satisfaction (β = 0.183, t = 3.306, p = 0.001), whereas Collectivism shows no substantial influence (β = –0.068, t = 1.694, p = 0.09). Overall, the findings suggest that LMS interfaces in Indonesia should prioritize efficient navigation, structured aesthetics, and clear hierarchical organization aligned with high power distance culture, providing practical insights for culturally responsive LMS design.